A socio-cultural and linguistic analysis of yemeni Arabic personal names - Abdul Wahed Qasem Ghaleb Al-Zumor, (Penerbitan UKM, 2009)
This study is an investigation in anthroponomy of a Yemeni community which may reflect the naming practices followed in some tribal regions of Yemen neighboring Saudi Arabia. The study aims at investigating personal names, particularly female names, as they look very striking to a person who does not know much about the culture of those regions. Almost 300 personal female names are collected by the researcher using questionnaire as the tool for data collection. The names are, then, classified into different categories on the basis of their sources. For instance, Saadah and the adjacent governorates (in Yemen) are famous for different weapons business, so, you can hear names like tomateek, canadah: types of gun or qunbulah: grenade). Such selection of names is indicative of the attitudes of the parents of the family and of the way they are associated with the nature and the atmosphere around them as suggested by the responses to the questionnaire. However, the changing social, political and linguistic influences on the land and the people of Saadah and the neighboring places (in Yemen) have left their impact on naming patterns. As a result, naming practices are changing. This study is a preliminary investigation in anthroponomy of the Yemeni community, to be precise in the north and north west part of the country. It is an attempt toward understanding anthroponomy as a branch of the science of Onomastics in the region in relation to sociolinguistics